The Imbalance Attitude of the Journalists in Six Chemical Castration Texts: An SFLCritical Discourse Analysis - Mustofa Kamal; Riyadi Santosa; Djatmika Djatmika (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This research investigates how journalists behave in texts. The analysis focuses on the exploitation of attitudinal lexis. This is qualitatively explored through attitude and graduation. The data sources were columns of news, taken from an online version of The Jakarta Post on June sixth 2016. Having been selected using criterion-based sampling technique, the sources of data resulted in six chemical castration texts. The procedure of investigation consists of domain, taxonomic, componential, and cultural value analysis. The result shows that journalists are relatively subjective in reporting news by unbalancing the pros and cons, relatively inconsistent in work from delivering news to criticizing government officials, and relatively provocative by up-scaling critical evaluations against the government policy on sex offenders.